Biodiversity and species extinction: categorisation, calculation, and communication. Issue 4 (1st October 2020) - Turnhout, Esther; Purvis, Andy
ABSTRACT: After the launch of the Global Assessment of the Intergovernmental Platform for Biodiversity and Ecosystem Services (IPBES) in May 2019, the message that 1 million species are threatened with extinction made headlines in news and social media across the world. These headlines also resulted in critical responses that questioned the credibility of this number and – by extension – the Global Assessment report and the institution of IPBES. In this article, we – as two authors of the Global Assessment – draw lessons from the GA about how to represent biodiversity in assessments and how biodiversity knowledge can inform effective and legitimate actions that contribute to conservation as well as equity, justice, and human well-being. Specifically, we highlight the inherent multiplicity of meanings and definitions of biodiversity to reflect on the limitations of using species richness and extinction as proxies for biodiversity and biodiversity loss. It is crucial to communicate clearly and in a balanced way that biodiversity loss is broader than species extinction, and how this broader loss of biodiversity jeopardises human wellbeing irrespective of whether species die out. Consequently, the post-2020 biodiversity framework will require multiple targets around not only species extinction but also broader biodiversity loss and human well-being.